Recovery of Copper by Using Flotation Techniques and Microbe- Mineral Surface Interaction - Prasad Babu, K.; S.K.Rao Patnaik, K.; Shyam sunder, R. (International Journal of Engineering and Technology, 2018)
According to research paper, copper recovery from high grade copper was make an effort treating with a chemolithotrophic microorganism, and Acidithiobacillus ferrooxidans bacteria. The aim of the presentÂ study is to understand the changes in Copper ore beneficiation based on surface chemical properties of bacteria during adaptation to high grade copper minerals and the projected consequences in flotation and bio-flotation processes .The utility of bio processing in the beneficiation of Copper ore through bio-flotation is demonstrated in this work. An autotroph Thiobacillusferroxidansbacteria is adapted to high grade mixed copper ore sample, which was supplied from HCL Malanjkhand Copper Plant, Open cast mines. According to the procedure the collection and activation of the bacterial strains of Acidithiobacillus ferrooxidans.In 9K media Culture bacteria was developed, added sufficient amount of nutrients and agitated the culture to enhance the growth at room temperature. Copper sample was adapted by repeated subcultures of bacteria. The surface characteristics were studied Zeta Potential by analysis at different Ph values and different time intervals. After that the samples were analyzed by Chemical Analysis in the Laboratory for the percentage of the Copper recovered from each sample and also calculated rate constant (k) by using Flotation kinetics. From the studies it was observed that the mineral adapted cells became more hydrophobic as compared to un adapted cells during bio-flotation .It was also noticed that there was no significant changes in the surface charge of bacteria before and after adaption. If the adaption of bacteria is high then the recovery of Copper is more.Â Â Â